Occupational Health and Safety, Work Discipline, Leadership Style Affect Employee Performance - Rostina, Cut Fitri; Muhani, Devy; Sinaga, Tresha (Universitas Pendidikan Ganesha, 2020)
Human Resources is one of the most important things in managing an existing system within an organization or company. Therefore, human resources must be managed as well as possible to improve quality in the company. This study aims to analyze the effect of occupational safety and health, work discipline, and leadership style on employee performance. This type of research is a quantitative descriptive study. This research is explanatory, or so-called pure research or main research. The number of samples in this study were 261 people who were determined using simple random sampling technique. The data in this study were collected using an instrument in the form of a questionnaire. Data were analyzed using t-test and f-test. The results showed that in partially the occupational safety and health variables have a significant effect on performance which can be seen from the t-count(-2.876) higher than t-table (1.65), the work discipline variable has a significant effect on performance can be seen from the t-count (11,177) higher than t-table (1.65), and the variable leadership style has a significant effect on performance which can be seen from the t-count(3.849) higher than t-table (1.65). The variables of occupational safety and health, discipline, and leadership style simultaneously have a significant effect on employee performance, as seen from F-count (84,116) higher than F table (2.65) and a significance probability of 0.000 smaller than 0.05. So, it can be concluded that occupational safety and health, work discipline, and leadership style simultaneously have a significant influence on employee performance.